Determination of Traffic Induced Noise Pollution and Its Impact on The Citizens in The Zakho City Area - Basher, Yaldz Mohammed; Ramadhan, Shireen H (Science Journal of University of Zakho, 2022)
The current paper deals with determining the level of noise pollution in the area of ​​the Zakho city and its regions Impact on city residents. In this study, noise levels were measured with a digital sound level meter in seven different places in Zakho from 9:00 AM to 8:00 PM during working days. The time-weighted average noise level was measured on the roadside. The data collected was analyzed to calculate the average, maximum, and minimum noise level in decibels (dB) with respect to traffic volume. It was observed from the study that the highest roadside noise level in Zakho city was 96.1 dB found in the traffic (A) at the evening, which exceeded the acceptable limit of 60 dB set by the Government of Iraqi region and the minimum sound level of 51.5 dB was recorded in Traffic (D) area at the morning. The highest mean value is 88.63dB found in traffic (A) at the evening and the lowest median value is 66.5dB found in the Traffic (D) at the morning. During the study and according to Questionnaire survey, Noise health effects are the health consequences that high levels of noise have on health. It causes hearing loss, high blood pressure, and decreased blood flow to the heart, bowel movements, sleep disturbance, and an increase in work accident rates.